Federal Tax Policy for the 1990's: The Prospect from the Hill - Minarik, Joseph J. (American Economic Review, 1992)
The performance of the economy has been characterized as unacceptable by President George Bush, and that opinion is widely held. However, the nature of the problem is a matter of controversy. Some observers believe that the tax system is to blame. In my opinion, we do not have a tax problem; we have a much broader economic problem. One reason for a tax bill now would be the recession that began in the middle of 1990 and may not yet have ended. Countercyclical stimulus is a classic purpose of tax policy. However, it is possible to make the classic error of countercyclical fiscal policy and hit the accelerator only after recovery has begun. We might also add to the deficit and the national debt in the long run, raise long-term interest rates, and thereby reduce investment. Concern about the long run is well taken. Growth was extremely slow for a full year before the recession officially began. In fact, there have been 11 consecutive quarters of annualized real growth less than 2.5 percent, and that string is about to be rounded to three full years. Many forecasters, extrapolating from the expansion of the 1980's, believe that long-term potential real growth is less than 2.5 percent per year-well below the actual growth enjoyed in the 1950's and the 1960's. Some economists allege that slow recent growth and the recession were caused by failures of tax policy, specifically the Tax Reform Act of 1986 and the reconciliation bill of 1990. However, the following sectoral analysis suggests that these indictments are incorrect. A decline in real consumption in mid-1990 was probably the major single contributor to the recession. Few would allege that structural flaws in tax policy have decreased consumption; indeed, the mantra of a vocal group of policy pundits has been that the tax code has encouraged consumption. Some analysts have tried to blame the recession on either the revenue increases included in the 1990 reconciliation bill or the luxury tax included in that bill. Such claims are absurd. The deficit-reduction agreement was not even legislated until October 1990 (two months after the recession began) and its near-term fiscal impact was small. The notion that recession was brought on by declines in demand for expensive boats (whose sales peaked in 1987) and expensive automobiles (most of which are imported) makes even less sense. In the aggregate, investment has been one of the bright spots of the economy, and has held up in this recession better than in others. In the long term, the picture is even brighter. Equipment investment is stronger than total investment, with gross real investment in equipment matching its historical peak. The weak segment is investment in commercial structures which many economists would agree should not be taxfavored in pursuit of long-term economic growth and which were drastically overbuilt in the 1980's. Government budgets are restrictive, partly because of federal restraint, but even more because states and localities are cutting * Budget Committee, U.S. House of Representatives, 220 O'Neill House Office Building, Washington, DC 20515-6065. Albert J. Davis, Joseph E. Stiglitz, and Emil M. Sunley provided helpful comments but should not be implicated in any errors or omissions.